2015
DOI: 10.1161/hypertensionaha.115.05398
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Rictor in Brain and Fat Alters Peripheral Clock Gene Expression and Increases Blood Pressure

Abstract: Abstract-The mammalian target of rapamycin complex 2 (mTORC2) contains the essential protein RICTOR and is activated by growth factors. mTORC2 in adipose tissue contributes to the regulation of glucose and lipid metabolism. In the perivascular adipose tissue, mTORC2 ensures normal vascular reactivity by controlling expression of inflammatory molecules. To assess whether RICTOR/mTORC2 contributes to blood pressure regulation, we applied a radiotelemetry approach in control and Rictor knockout (Rictor aP2KO ) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…However, it seems that many of the negative adverse effects of rapamycin treatment are mediated by inhibition of mTORC2 (5). It has been recently shown that Rictor has positive effects on a variety of functions involved in whole-body homeostasis (6)(7)(8)(9)(10). Although at this time, the role of mTORC2 in the regulation of longevity is uncertain (11), several lines of evidence imply that mTORC2 may have opposite effects on aging compared with mTORC1.…”
mentioning
confidence: 99%
“…However, it seems that many of the negative adverse effects of rapamycin treatment are mediated by inhibition of mTORC2 (5). It has been recently shown that Rictor has positive effects on a variety of functions involved in whole-body homeostasis (6)(7)(8)(9)(10). Although at this time, the role of mTORC2 in the regulation of longevity is uncertain (11), several lines of evidence imply that mTORC2 may have opposite effects on aging compared with mTORC1.…”
mentioning
confidence: 99%
“…We therefore speculate that during metabolic diseases such as obesity the diurnal variation of Rictor is dysregulated and perturbs vascular physiology. In line, we have shown that ablation of Rictor in adipose tissue and brain results in impaired PVAT function resembling a phenotype which is similar to metabolic disease and impaired diurnal blood pressure regulation possibly by affecting inflammatory molecule and natriuretic peptide expression [7,19].…”
Section: Discussionmentioning
confidence: 57%
“…The method was performed essentially as described earlier [7]: RNA from PVAT, EFAT and BAT was extracted using RNeasy ® lipid tissue kit and from thoracic aortas using RNeasy ® fibrous tissue kit, according to the protocol of the manufacturer (Qiagen, Hombrechtikon, Switzerland) respectively. DNA was removed using an on- Each reaction was performed in duplicates using Bio-Rad CFX96 Real-Time System and iQ™ SYBR ® Green Supermix (BioRad, Hercules, CA, USA) and specific mouse primers.…”
Section: Rna Isolation Reverse Transcription and Quantitative Real-tmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila , TOR rhythms are also found in the brain and in particular the ventral lateral neurons ( Zheng and Sehgal, 2010 ; Kijak and Pyza, 2017 ). In peripheral tissues, mTOR activities are rhythmic in the liver, cardiac and skeletal muscles, adipocytes, and retinal photoreceptors ( Huang et al, 2013 ; Jouffe et al, 2013 ; Shavlakadze et al, 2013 ; Khapre et al, 2014 ; Drägert et al, 2015a , b ; Lipton et al, 2015 , 2017 ; Chang et al, 2016 ). Interestingly, mTOR also shows circadian rhythms in human osteosarcomas, mouse renal carcinomas as well as human breast cancer cells ( Zhang et al, 2009 , 2018 ; Okazaki et al, 2014 ).…”
Section: Mtor and The Circadian Clockmentioning
confidence: 99%